Pengaruh Model Pembelajaran Student Facilitator and Explaining (SFAE) terhadap hasil Belajar Peserta Didik Kelas V pada Mata Pelajaran Matematika Berbatuan Media Pop-UP Book di SD Al Ittihadiyah Mamiyai - Lubis, Fani Anggita; Siregar, Nurdiana; Siregar, Lailatun Nur Kamalia (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by the mathematics learning process. Educators sometimes do not use varied learning models, so students experience boredom in the learning process. Apart from that, teachers still use conventional learning methods which direct the learning process more from the teacher to the students. The aim of this research is to determine the effect of the student facilitator and explaining learning model on the mathematics learning outcomes of fifth grade elementary school students. The design of this research is a quasi-experimental research with a non-equivalent pre-test and post-test control group. The population studied in this research were all students from class I to class VI, totaling 142 people. The sample in this study used a non-probability technique with purposive sampling, namely a technique for determining samples selected based on certain criteria. The sample consisted of two classes V-A and V-B at SD Al-Ittihadiyah consisting of 38 students. The data collection techniques used by researchers are documentation and tests, namely giving pre-tests and post-tests. The research results, as determined by an independent t-test, showed that the average value for the experimental class was 76.86 with a standard deviation of 9.372. The average value for the control class is 67.82 with a standard deviation of 9.926. This shows that the average score for students in the experimental class who participated in the student facilitator and explaining learning model showed a higher level of improvement in their academic performance compared to students in the control class, who received conventional teaching. The sig (2-tailed) value of 0.007 is smaller than 0.005, which indicates that there is a statistically significant impact of the student facilitator and explaining learning model on students' academic achievement in mathematics at Al-Ittihadiyah Elementary School